Teaching mathematics in ancient Egypt - Živanović Milan V. (Sinteze, 2012)
There exists no science the history of which begins with its official promotion into a new discipline. The sources of a science accumulate through numerous activities interwoven with other sciences in the preceding period. When enough material has been obtained in this way, material which in the classification of sciences stands apart by its subject, objectives and methodology of research, we can talk about the birth of a new science. Mathematics, as a science, rightfully occupies central position in the development of civilization. This assumption was constantly emphasized through time in the words and actions of its most prominent representatives. Therefore, it is absurd that it should be severely neglected in education, which is often justified by its being 'unpopular', or even worse, through forced preference given to other sciences resulting from power struggles within administrative structures of various levels of education planning. This paper aims to promote mathematics as a science and advocate its place in contemporary education by providing a historical account of its beginnings as a school subject. Specifically, the study analyses ancient writings prepared for teaching mathematics: the Moscow and Ahmes Papyrus.